Ash Evaluation of Indonesian Coal Blending for Pulverized Coal-Fired Boilers. (14th December 2021) - Hariana,; Prismantoko, Adi; Ahmadi, Ganda Arif; Darmawan, Arif
Abstract : Coal calorific value is one of the main considerations for using coal as a power plant fuel. In addition, the requirements for indications of slagging and fouling are also important to maintain combustion efficiency. However, coal power plants often experience problems in boiler operations due to the use of certain types of coal, even though they have a relatively high calorific value. This research investigates the effect of coal blending on ash fouling and slagging in an experimental investigation using a drop tube furnace with or without additives. Five different types of coal from different locations have been used in this study. Pulverized low-rank coal samples are burned in a drop tube furnace at 1, 175°C with probe temperatures of 550°C and 600°C, corresponding to the combustion chamber of 600 MW power plants, including superheater and reheater areas. The ash particles' characteristics and material composition were also analyzed using scanning electron microscopy with energy-dispersive X-ray (SEM-EDX) and X-ray diffraction (XRD), respectively. All coal mixture combinations demonstrated potential as a fuel for power plants that use pulverized coal-fired boilers. Because of its capacity to reduce slagging and fouling potentials, combining coal blending with the use of chemical additives yielded the greatest results.